Σχεδιασμός επίγειου συστήματος αλυσοκίνησης για μεταφορά τρόλεϊ - Σταυρίδης, Μάριος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The aim of this thesis is the design of a ground conveyor chain that has a trolley on it, in an industrial factory. In the following chapters, details shows the steps that have been taken for the calculation of all the components and the material used in the construction from people with experience in this field. Initially, the power of the motor has been calculated to be able to move the platform and then depending on the motor power the dimensions of the sprocket and the chain as such as the pitch were estimated. Also, the dimensions of the bearing and the housing of the bearing were estimated, as the coupling that transfers the movement of the motor to the axis. All dimensions were taken from the catalogs of the company «RENOLD» and the dimensions of the bearing and the housing for the catalogs of the company «SKF»; which is reliable for use of their catalogs. Additionally, static analysis of the forces has been done with the help of «SolidWorks» software for the shaft and the base of the structure. A comprehensive plan has been made by the software «SolidWorks» which shows the whole conveyor chain system and the trolley in the platform. Finally, linear actuators have been placed in the system and their purpose is to change the trolley production line. Linear actuators receives the signal from proximity sensors who perceive the distance between the trolley and the sensor. As soon as the trolley is close to the sensor in a distance that we want, it initially sends signal to the motor to stop working, and then sends signal to the linear actuator to push the trolley to the next production line, and at the end sends again signal to the motor to start again. Finally, there were thoughts on possible improvements that could be made to the structure to improve the cost and safety.
Keywords: Ground; Conveyor chain; Trolley; Solid Works; Επίγεια; Αλυσιδοκίνηση; Τρόλεϊ